Narcissistic self-sorting and enhanced luminescence via catenation in water. (March 2022) - Chen, Q.; Lei, Y.; Wang, H.; Wu, G.; Xu, W.; Jiao, T.; Pan, Y.; Zhang, Q.; Zhang, Y.-M.; Liu, Y.; Li, H.
Abstract: Narcissistic self-sorting, namely that components are able to distinguish 'self' from 'non-self' during self-assembly, was accomplished via catenation by condensing multiple hydrazides and an aldehyde, or a hydrazide and multiple aldehydes in water. The underneath mechanism of this behavior relies on the corresponding homo [2]catenanes which are thermodynamically more favored than their hetero counterparts because the former containing two identical macrocyclic components are able to maximize the inter-component non-covalent forces. One of these catenanes contains four 4-phenylpyridinium units, which are often considered barely luminescent because of intramolecular rotations and vibrations that lead to non-radiative annihilation of their excited states. These intramolecular motions, however, are restricted upon integrating 4-phenylpyridiniums within the catenane architecture. As a consequence, compared to its non-interlocked counterparts, this catenane exhibits enhanced fluorescence, which represents a novel conceptual model for developing luminescent materials. Graphical abstract: Condensing a set of bisaldehyde and bishydrazide in acidic water selectively produces [2]catenanes containing only one type of macrocyclic components. The catenane exhibits enhanced fluorescence compared to its non-interlocked counterparts, which represents a novel conceptual model in attaining highly emissive nanoconstructs. Image 1